2014
DOI: 10.11648/j.jfns.20140204.16
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Breakfast Eating Habits and its Association with Cognitive Performance of Early Adolescents (11-13 Years) in Shebedino District, Sidama Zone, Southern Ethiopia

Abstract: Background: Regular consumption of breakfast is associated with improved cognitive performance and nutrient intake in adolescents. Despite breakfast's positive attributes, many children go to school without breakfast. The objective of this study was to assess the association between breakfast eating habits and cognitive performance among early adolescents aged 11-13 years old in the study area. Method: A cross sectional study was conducted from June to July 2012. Structured questionnaire was used to capture br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 37 publications
3
10
0
1
Order By: Relevance
“…Young adults are more linked with the beginning of puberty and cognitive maturity and consequently require additional nutrients for appropriate development. They are also allied with recurrent habit of skipping meals [4].Unhealthy, unbalanced eating habits and diseases induced by this age group were located in the first priority [5]. Eating habits and practices detected in young adults may have harmful effect on their health.…”
Section: Introductionmentioning
confidence: 99%
“…Young adults are more linked with the beginning of puberty and cognitive maturity and consequently require additional nutrients for appropriate development. They are also allied with recurrent habit of skipping meals [4].Unhealthy, unbalanced eating habits and diseases induced by this age group were located in the first priority [5]. Eating habits and practices detected in young adults may have harmful effect on their health.…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous studies examining the relationship between breakfast habit and academic performance/success of children and adolescents (15)(16)(17)(18)(19)(20). Our research was conducted to identify the relationship between breakfast quality index and academic success of primary-school refugee children.…”
Section: Discussionmentioning
confidence: 99%
“…The longitudinal study conducted among Australian children also revealed that over all academic achievement were higher in breakfast non-skippers than breakfast skippers [19]. A cross sectional study conducted in southern Ethiopia also shown that habit of skipping breakfast affected the cognitive performance of early adolescents [20]. This could be due to deficiency in maintaining adequate levels of glucose throughout the day which contributes to optimizing cognition.…”
Section: Discussionmentioning
confidence: 99%